Establishment of RCPA national guidelines for selective reporting of antimicrobials: processes, challenges and measuring the impact. (17th August 2022) - Graham, Maryza; Graves, Debra; Cooley, Louise; Elvy, Juliet; Kelley, Peter; Maley, Michael; Porter, Michelle; Robson, Jennifer; Turnidge, John
Abstract: Objectives: In 2016, The Royal College of Pathologists of Australasia (RCPA) initiated the formation of a working group comprising medical microbiologists to establish guidelines to assist Australian laboratories to implement selective and cascade reporting of antimicrobials—the first guidelines of this type in the world. Methods: A 2017 audit of antimicrobial reporting in Australian and New Zealand laboratories identified significant opportunities for improvement and standardization of selective reporting. Results: The first draft of the RCPA Selective Reporting Guidelines was circulated to all RCPA Microbiology fellows for feedback in August 2018 and the first version was published in February 2019. Subsequently, version two of the guidelines has recently been published in Australia, and New Zealand adapted these guidelines for formulation of their own national guidelines to accommodate local needs. Conclusions: Here we describe the processes, acceptance and challenges associated with the establishment of these guidelines and measurement of their impact.